2022
DOI: 10.1371/journal.pone.0268543
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor levels in tuberculosis: A systematic review and meta-analysis

Abstract: Background Changes in endothelial function are implicated in the spread of tuberculosis (TB). Studies suggest a role for the vascular endothelial growth factor (VEGF) in TB-related endothelial function changes. However, the findings of studies investigating the VGEF profile in TB are not consistent, and no formal systematic review and meta-analysis exists summarizing these studies. Methods We did a meta-analysis of studies assessing VEGF levels in patients with TB. A systematic search on June 25, 2021, was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…This demonstrated that a significant difference was observed in the complication incidence, indicating that total hip arthroplasty displayed a lower incidence of hipjoint functional complications. The same idea can be found in the study put forward by other scholars [40][41][42]. They have applied new methods in the study, and the conclusions drawn can also give some support to this study.…”
Section: Discussionsupporting
confidence: 72%
“…This demonstrated that a significant difference was observed in the complication incidence, indicating that total hip arthroplasty displayed a lower incidence of hipjoint functional complications. The same idea can be found in the study put forward by other scholars [40][41][42]. They have applied new methods in the study, and the conclusions drawn can also give some support to this study.…”
Section: Discussionsupporting
confidence: 72%
“…It is a useful biomarker of disease in TBM and is thought to cause BBB dysfunction through its effects on the ECM and tight junctions. Plasma and CSF VEGF-A concentrations are significantly higher in TBM patients than controls although not associated with outcome ( 40 ). In a study looking for a CSF biosignature for TBM using proteomics in HIV-uninfected children, a combination of VEGF-A, IFNγ and myeloperoxidase had a sensitivity and specificity of 91.3% and 100% respectively compared to a heterogeneous non-TBM group, suggesting VEGF-A as an important contributor in TBM pathogenesis ( 41 ).…”
Section: The Host Immune Response Against Tbmmentioning
confidence: 99%
“…Tumor removal or medical therapies that reduce vascular permeability will resolve edema and cysts, suggesting that the tumor is the source of edema that precedes cyst formation. [35] The underlying idea of modern cancer biology is simple: nearly all mammalian cells share comparable molecular networks that drive cell proliferation, differentiation, and death. The prevalent view, which underpins cancer research, holds that alterations in these networks cause normal cells to become malignant at the molecular, biochemical, and cell levels and that each cell has a set number of models that are very susceptible to change.…”
Section: Breakdown Enzymesmentioning
confidence: 99%
“…CSF VEGF levels in patients without persisting neoplastic or infectious diseases were less than the detection limit of 25ppm/ml. [35]…”
Section: Bacteria Sampling Of Brain Cancer In Csfmentioning
confidence: 99%